ANALISIS PENGARUH NET PROFIT MARGIN (NPM) RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM - Muhamad Jusmansyah (Universitas Pamulang, 2018)
AbstractThis study aims to analyze the effect of Net Profit Margin, Return on Equity and Earning Per Share on Stock Price of manufacturing companies listed on Indonesia Stock Exchange in observation year 2012 - 2016.Using a linear regression analysis method is assisted with the use of the SPSS program version 23 which utilizes secondary data from a sample of 15 (fifteen) chemical industry sector group manufacturing companies that have been listed on the Indonesia Stock Exchange for the 2012 to year period 2016. While the sampling method used is purposive sampling method. This study obtained the following results: (1) Net Profit Margin influential on Stock Price, (2) Return On Equity effect on Stock Price, (3) Earning Per Share effect on Stock Price, (4) ) The results of regression analysis simultaneously influenced the result that Earning Per Share effect on Stock Price. As for Net Profit Margin and Return on Equity does not affect the stock price. Keywords: NPM, ROE, EPS, on Stock Price.